Modulation of endoglin expression in islets of langerhans by VEGF reveals a novel regulator of islet endothelial cell function. (December 2016) - Clarkin, Claire; Mahmoud, Marwa; Liu, Bo; Sobamowo, Emmanuel; King, Aileen; Arthur, Helen; Jones, Peter; Wheeler-Jones, Caroline
Background Endoglin/CD105 is an auxiliary receptor for transforming growth factor-β with established roles in vascular remodelling. It has recently been shown that heterozygous endoglin deficiency in mice decreases insulin secretion in an animal model of obesity, highlighting a potential role for endoglin in the regulation of islet function. We have previously identified two different populations of endoglin expressing cells in human and mouse islets which are: (i) endothelial cells (ECs) and (ii) islet mesenchymal stromal cells. The contribution of islet EC endoglin expression to islet development and sensitivity to VEGF is unknown and is the focus of this study. Results In vitro culture of mouse islets with VEGF164 for 48 h increased endoglin mRNA levels above untreated controls but VEGF did not modulate VEGFR2, CD31 or CD34 mRNA expression or islet viability. Removal of EC-endoglin expression in vivo reduced islet EC area but had no apparent effect on islet size or architecture. Conclusion EC-specific endoglin expression in islets is sensitive to VEGF and plays partial roles in driving islet vascular development, however such regulation appears to be distinct to mechanisms required to modulate islet viability and size.